2015
DOI: 10.1177/2050640615581967
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of laparo‐endoscopic resections of colorectal neoplasia: A systematic review

Abstract: Objective: The purpose of this review is to assess the efficacy and safety of laparo-endoscopic local resections for colorectal lesions not suitable for endoscopic resection. Summary background data: The combined laparo-endoscopic approach has been proposed for large colorectal lesions unsuitable for endoscopic resection, in order to reduce morbidity of common laparoscopic resection. However, data on the efficacy and safety of laparo-endoscopic local resections are still controversial. Methods: An Embase searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…in a systematic review of 11 studies found that the mean complication rate after LACP was 7.9%. In our study we had a complication rate of 4.8% and mean hospital stay length was comparable with other studies [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…in a systematic review of 11 studies found that the mean complication rate after LACP was 7.9%. In our study we had a complication rate of 4.8% and mean hospital stay length was comparable with other studies [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 88%
“…Only 45.5% of patients were admitted for colonoscopy follow-up; moreover, the adenoma recurrence rate was almost 10-fold higher than in previous papers [10, 14]. One tenth of all follow-up patients had adenocarcinoma recurrence in a resected polyp with high-grade dysplasia that was subjected to radical treatment.…”
Section: Discussionmentioning
confidence: 85%
“…По данным большинства имеющихся в литературе публикаций, длительность операции и сроки пребывания пациентов в стационаре после гибридных лапаро-эндоскопических вмешательств оказались меньше, в сравнении с аналогичными показателями после лапароскопических сегментарных резекций толстой кишки [18][19][20]27,33], что подтверждается результатами исследований, включенных в данный метаанализ [16,17,24,28]. [2]. В данной работе частота повторных операций после гибридного лапаро-эндоскопического удаления опухоли для достижения онкологической радикальности составила 7,9%.…”
Section: Discussionunclassified
“…[ 11 , 12 ]. Despite the use of laparoscopy, colonic resection is associated with perioperative morbidity of up to 30% [ 13 ] and should be confined to indications unsuitable for endoscopic resections.…”
Section: Introductionmentioning
confidence: 99%